Transcatheter Aortic Valve Implantation in Post Coronary Artery Bypass Graft Patient - Adhikari, Chandra Mani; Bogati, Amrit; Timalsena , Birat Krishna; Safi , Md. Sajjad; Thapa , Pratik; Ghimire, Vijay; Yadav, Rahul; Prajapati, Dipanker (Journal of National Heart and Lung Society Nepal, 2025)
Patients with a prior coronary artery bypass graft and severe aortic stenosis represent a unique subset. Surgical aortic valve replacement is a strong contraindication in patients with severe aortic stenosis who have a history of coronary artery bypass grafting. In this case report, we share our experience with transcatheter aortic valve implantation in a post-coronary artery bypass graft patient at Shahid Gangalal National Heart Center, an emerging transcatheter aortic valve implantation center in Nepal.